Dietary patterns and quality of life among night-shift nurses in tertiary hospitals in Hangzhou: a cross-sectional analysis - Liang, Guanmian; Hua, Rongyu; Yang, Fangying (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to examine the dietary patterns of nurses working night shifts in tertiary hospitals in Hangzhou and to assess the association between these patterns and quality of life. The objective is to provide evidence from a nutritional standpoint to inform health promotion strategies within the nursing workforce.MethodA cross-sectional design was employed. A total of 1,024 valid questionnaires of dietary intake data were collected using the simplified Food Frequency Questionnaire (FFQ25), and quality of life was assessed via the 36-Item Short Form Survey (SF-36). Factor analysis was utilized to identify major dietary patterns. One-way analysis of variance was conducted to explore differences in quality-of-life scores across dietary pattern groups.ResultsThree primary dietary patterns were identified: Traditional, Western, and Balanced. The traditional and balanced dietary patterns were associated with higher SF-36 scores across most dimensions compared to the western dietary pattern, with the exception of the general health dimension. Statistically significant differences were observed between the Traditional and Western patterns in physical functioning, emotional state, health transition, and general health (p < 0.05). Comparisons between the Balanced and Western patterns revealed significant differences in general health and health transition (p < 0.05), with no significant differences in other domains.ConclusionDistinct dietary patterns were observed among nurses engaged in night-shift work, with associations noted between specific patterns and quality-of-life outcomes. These findings suggest that dietary behavior may serve as a proxy for broader health-related behaviors. Interventions targeting nutritional habits may contribute to enhanced quality of life and support comprehensive health promotion strategies among nursing personnel.